Konsep Pendidikan Multikultural Penanggulangan Terorisme Dalam Buku Pendidikan Agama Islam Dan Budi Pekerti Kurikulum Merdeka Pada Jenjang SMA - Indah Utari, Muslikha (CV. Satria Jaya, 2023)
The rise of acts of terrorism in the name of Islam in Indonesia and in the world, has drawn a lot of criticism and scrutiny and has placed Muslims as the party to blame. The method in this study uses a type of library research (library research). The research data consists of primary data and secondary data. Data was collected using documentary techniques, which were collected from books, papers or articles, magazines, scientific journals and newspapers. Data analysis techniques include deductive and inductive. The results of this study found: 1) The concept of Counter-Terrorism Education as an effort to prevent terrorism through education is the basis of philosophy in education, moral and religious values. 2) The concept of Islamic Religious Education and Moral Character in the Free Curriculum Islamic Religious Education and Moral Education taught in schools are subjects that aim to produce students who have a religious spirit and obey their religious orders. direct students to become people of faith and carry out good deeds according to their respective abilities.